Whole-genome-based characterization of three human Rotavirus C strains isolated from gastroenteritis outbreaks in Western India and a provisional intra-genotypic lineage classification system. (5th June 2019) - Joshi, Madhuri S.; Walimbe, Atul M.; Dilpak, Sanmati P.; Cherian, Sarah S.; Gopalkrishna, Varanasi
Abstract : The number of whole-genome sequences of human rotavirus C (RVC) strains available in public databases is recently increasing. Thus far from India only a single whole genome of human RVC of a sporadic case was available. In this study, nearly full-length genome sequencing and phylogenetic analyses of three RVC strains isolated from three different gastroenteritis outbreaks during 2010–2014 in Western India was carried out. Further, an intra-genotypic lineage classification system for human RVCs based on the nucleotide divergence cut-off values was proposed by using the algorithm of the Rotavirus Classification Working Group. Two lineages could be defined for all the genes except the VP7 gene and the M3 VP3 genotype. Provisional classification of the lineages indicated the absence of reassortment events in the genomic constellation of Indian strains, contrary to earlier reports. The comparatively higher variability of the NSP1, NSP3, NSP5 and M2 VP3 genotype, emphasizes their utility in lineage classification.